Influence of Intrinsic and Extrinsic Motivation on Job Satisfaction of Implementing Nurses at RSU Royal Prima Marelan in 2021 - Lin Shikun; Florenly Florenly; Liena Liena; Johannes Bastira (Budapest International Research and Critics University, 2021)
Job satisfaction is an individual's general attitude toward the work he or she does. A person with a high level of job satisfaction shows a positive attitude towards his or her job, while someone dissatisfied with his work shows a negative attitude towards his work. Nurses are the spearhead and have an important position in producing the quality of health services in hospitals because the services they provide are carried out for 24 hours continuously. The purpose of this study was to determine the effect of intrinsic and extrinsic motivation on the job satisfaction of the managing nurse. This type of research is a non-experimental quantitative study with a descriptive approach (cross-sectional survey) and associative analysis, conducted at Royal Prima Marelan Hospital, March 2021. The study population of 377 people, determining the number of samples with the formula SEM (Structural Equation Modelling) was not obtained 100 samples. The sample determination technique used in this study is to use a purposive sampling approach. Bivariate analysis with Chi-Square test, and multivariate with multiple logistic regression with p-value (0.05). The results of the study that simultaneously, the variable Award (X1), Achievement (X2), Supervision (X3), Responsibility (X4), has an influence on the variable of job satisfaction with p-value < 0.05. While the variable Wage (X5), Work Environment (X6), Status (X7), with a p-value of > 0.05, does not affect the variable job satisfaction of the managing nurse at Royal Prima Marelan Hospital. The results of the multivariate analysis, that from independent variables namely Awards, Achievement, Supervision, Responsibility, which allegedly affect job satisfaction the most influential is the variable of responsibility with a p-value of 0.017 < 0.05. Finally, the OR value obtained is 7,516, meaning a high sense of responsibility, which has a 7,516 times chance of affecting the level of job satisfaction of employees at Royal Prima Marelan Hospital.